Non-invasive ventilation in neonates: a review of current literature - Viraraghavan Vadakkencherry Ramaswamy; Risha Devi; Gunjana Kumar (Frontiers Media S.A., 2023)
Moving from an era of invasive ventilation to that of non-invasive respiratory support, various modalities have emerged resulting in improved neonatal outcomes. Respiratory distress is the commonest problem seen both in preterm and term neonates, and the use of appropriate respiratory support could be lifesaving. This article reviews the currently available non-invasive ventilation (NIV) strategies in neonates including nasal continuous positive airway pressure, nasal intermittent positive pressure ventilation (NIPPV), bi-level CPAP, heated humidified high flow nasal cannula, nasal high-frequency ventilation (NHFV) and non-invasive neutrally adjusted ventilatory assist (NIV-NAVA). Though multiple systematic reviews and meta-analyses have indicated the superiority of synchronized NIPPV over the other forms of non-invasive respiratory support in neonates, there is no single NIV modality that universally suits all. Hence, the choice of NIV for a neonate should be individualized based on its efficacy, the disease pathology, resource settings, the clinician's familiarity and parental values. Future studies should evaluate emerging modalities such as NIV-NAVA and NHFV in the respiratory management of neonates as the evidence pertaining to these is insufficient.